Brand Image dan Personal Branding Owner dalam Industri Hijab: Studi Kasus Keputusan Pembelian Hijab Lafiye - Balqis Bintang Paramita; Sri Indriani; Emmalia Adriantantri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the influence of brand image and Sashfir's personal branding on the purchase decisions of Lafiye hijab products. It addresses the growing phenomenon of social media influencers shaping consumer behavior, particularly in the modest fashion industry. Using a quantitative approach, data were collected through purposive sampling from 110 respondents who follow Sashfir on social media and have provided reviews about their purchasing experiences with Lafiye products. Multiple linear regression analysis was employed to examine the partial and simultaneous effects of the independent variables on purchase intention. The results indicate that both brand image and personal branding have a positive and significant impact on purchase decisions, with brand image exerting a stronger influence. These findings highlight the importance of developing personal branding strategies and strengthening brand image for business owners in the fashion industry. The study provides practical insights for digital marketing strategies and recommends future research with more inclusive questionnaire distribution to enhance respondent representation.